Prelabour Caesarean Section following IVF/ICSI in Older-Term Nulliparous Women: Too Precious to Push? - E. Gillet; E. Martens; G. Martens; H. Cammu (Journal of Pregnancy)
Objective. To compare prelabour caesarean section (CS) rates in older nulliparous women with a term singleton baby in cephalic presentation conceiving spontaneously and through IVF/ICSI. When the latter women would ask for CS, how willing are gynaecologists to comply with that request? Methods. A population-based retrospective (1995–2009) cohort study, conducted in Northern Belgium. A comparison of 1,866 nulliparous women pregnant after IVF/ICSI and 15,228 controls is made. An anonymous postal questionnaire is sent to all Belgian gynaecologists. Result. Both groups are comparable with respect to maternal age, gestational age, and birth weight. Prelabour CS is more often performed in women who conceived through IVF/ICSI compared to those who conceived spontaneously (9.2% versus 6.3%, P<0.001). One in five gynaecologists agrees with the maternal request. Conclusion. IVF/ICSI pregnancies in older nulliparous women more often end in a prelabour CS and a substantial number of gynaecologists go along with a nonmedical reason for CS.